2017
DOI: 10.1002/jcph.1050
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Momelotinib in Subjects With Hepatic or Renal Impairment

Abstract: Momelotinib is a Janus kinase 1/2 inhibitor in clinical development for the treatment of myelofibrosis. Two phase 1 open-label, parallel-group, adaptive studies were conducted to evaluate the pharmacokinetics of a single 200-mg oral dose of momelotinib in subjects with hepatic or renal impairment compared with healthy matched control subjects with normal hepatic or renal function. Plasma pharmacokinetics of momelotinib and its major active metabolite, M21, were evaluated, and geometric least-squares mean ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…The safety profile of momelotinib and trametinib at the doses tested were generally consistent with the known safety profile of each agent. The PK analysis was generally comparable with previous evaluations 11 and showed that maximum momelotinib plasma concentrations were approximately 300 ng/mL (equal to 0.72 μmol/L), which is below levels required to inhibit TBK1 kinase activity. 3 …”
Section: Discussionsupporting
confidence: 77%
“…The safety profile of momelotinib and trametinib at the doses tested were generally consistent with the known safety profile of each agent. The PK analysis was generally comparable with previous evaluations 11 and showed that maximum momelotinib plasma concentrations were approximately 300 ng/mL (equal to 0.72 μmol/L), which is below levels required to inhibit TBK1 kinase activity. 3 …”
Section: Discussionsupporting
confidence: 77%
“…PK analysis was generally comparable to prior evaluations [16, 20]. Maximum momelotinib plasma concentrations were approximately 300 ng/mL (equal to 0.72 μmol/L).…”
Section: Discussionsupporting
confidence: 67%
“…Erlotinib PK were not affected by momelotinib, whereas the momelotinib maximum concentration and exposure were higher than previously reported with a prolonged terminal elimination half-life [35]. In addition, C max and AUC tau of the major metabolite GS-644603 were several-fold lower than previously reported [35][36][37][38]. Erlotinib is a potent inhibitor of aldehyde oxidase [39], which is necessary for the formation of GS-644603 [40], perhaps accounting for the low levels of GS-644603 observed in this study.…”
Section: Discussioncontrasting
confidence: 65%